Prospective study to determine accuracy of rapid serological assays for diagnosis of acute dengue virus infection in Laos. - Blacksell, S; Bell, D; Kelley, J; Mammen, M; Gibbons, R; Jarman, R; Vaughn, D; Jenjaroen, K; Nisalak, A; Thongpaseuth, S; Vongsouvath, M; Davong, V; et al. (2007)
There is an urgent need for accurate and simple dengue virus infection diagnostic assays in limited-resource settings of dengue endemicity, to assist patient management. Using a panel of reference samples (S. D. Blacksell, P. N. Newton, D. Bell, J. Kelley, M. P. Mammen, D. W. Vaughn, V. Wuthiekanun, A. Sungkakum, A. Nisalak, and N. P. Day, Clin. Infect. Dis. 42:1127-1134, 2006), we recently evaluated eihgt commercially available immunochromatographic rapid diagnostic tests (RDTs) designed to detect dengue virus-specific immunoglobulin M (IgM) and/or IgG. We found that 6/8 RDTs had sensitivities of less than 50% (range, 6 to 65%), but specificities were generally high. Here, in conjuction with dengue virus serotyping by reverse transcriptase PCR and in the limited-resource setting of Laos, where dengue virus is endemic, we evaluated the same eight RDTs against a previously validated dengue IgM/IgG enzyme-linked immunosorbent assay for diagnosis of acute dengue virus infection. Paired serum samples were collected from 87 patients, of whom 38 had confirmed dengue virus infections (4 had primary infections, 33 had secondary infections, and 1 had an infection of indeterminate status). RDT sensitivity was low, with 7/8 RDTs having admission sample sensitivities of less than 20% (range, 4 to 26%). The majority (6/8) of the RDTs, demonstrated high specificity (>95%). Kappa statistic values ranged from 6 to 54% for the RDTs, demonstrating poor to moderate variation between three operators. No RDT adequately differentiated between primary and secondary dengue virus infections. The findings of this study suggest that currently available RDTs based on the detection of IgM antibodies for the diagnosis of acute dengue virus infections are unlikely to be useful for patient management.